Negotiating Imitation: Examining the Interactions of Consultants and Clients to Understand Institutionalization as Translation. (9th June 2019) - Gill, Michael J.; McGivern, Gerry; Sturdy, Andrew; Pereira, Sandra; Gill, David J.; Dopson, Sue
Abstract: Organizational scholars increasingly view institutionalization as a process through which actors adapt or translate seemingly successful practices in a field to create variations that are specific to their own organization. Yet little is known about how outsiders who seek to diffuse 'best practice' affect translation. We examined interactions between management consultants and their clients in two different consulting projects, which focused on embedding the practice of 'lean' in one and the practice of a quality improvement framework in the other. Our findings provide insights into the processes of translation through which promoters and adopters iterate at different stages to reach a compromise, illuminating how the evolution of an imported practice signals the outcome of a negotiation. Furthermore, we demonstrate that management practices are not translated in isolation but enveloped by peripheral practices that are adopted by association. We highlight how the peripheral practice of benchmarking, in both cases, was rarely contested or negotiated and thus proved more resistant to translation. Our analysis allows us to unpack the agency inherent within translation‐as‐negotiation and integrate research on diffusion and translation.